Effect of microwave assisted extraction on yield and protein characteristics of soymilk. (December 2019) - Varghese, Taruna; Pare, Akash
Abstract: Microwave assisted extraction (MAE) has been investigated for its potential to aid in extraction of soymilk from soybeans. A batch type grinding cum microwave heating unit was specifically designed and developed for this purpose. MAE of soymilk has resulted in significant increase (p < 0.05) in extraction yield (24%) and protein content (44.4%) as compared to conventional soymilk. Protein characteristics such as protein solubility and protein digestibility of extracted soymilk also showed significant increase (p < 0.05) with respect to conventional milk. The influence of microwave process parameters including microwave power level (540–810W), target temperature (70–90 °C) and stirring speed (140–180 RPM) on protein characteristic of soymilk were analysed. Microwave power level and target temperature were significant (p < 0.05) parameters for the extraction process. The optimal MAE conditions were power level of 675W, target temperature of 80 °C and stirring speed of 160 RPM. Highlights: Microwave assisted extraction has been proven as an effective method to increase extraction yield and quality of soymilk. Yield, protein content and protein solubility of soymilk was increased by 24%, 44.4% and 94.6% respectively by this method. Microwave power and target temperature were significant for yield and quality of soymilk. SEM imaging revealed increased breakdown of soybean cell wall structure. This attributes to the success of MAE.